2016
DOI: 10.1186/s40643-016-0092-x
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of biochars produced from peanut hulls and pine wood with different pyrolysis conditions

Abstract: Background: Application of modern biomass pyrolysis methods for production of biofuels and biochar is potentially a significant approach to enable global carbon capture and sequestration. To realize this potential, it is essential to develop methods that produce biochar with the characteristics needed for effective soil amendment.Methods: Biochar materials were produced from peanut hulls and pine wood with different pyrolysis conditions, then characterized by cation exchange (CEC) capacity assays, nitrogen ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…These results demonstrated that the surface area and pore volume of Mba are more superior than those of Sba. Compared to those reported elsewhere, 168 m 2 /g for wood chip biochar produced at 600 °C 19 and 186 m 2 /g for yellow pine biochar 20 , the surface area of Mba is higher. A larger surface area means more porous structures within biochar 21 .…”
Section: Resultscontrasting
confidence: 77%
“…These results demonstrated that the surface area and pore volume of Mba are more superior than those of Sba. Compared to those reported elsewhere, 168 m 2 /g for wood chip biochar produced at 600 °C 19 and 186 m 2 /g for yellow pine biochar 20 , the surface area of Mba is higher. A larger surface area means more porous structures within biochar 21 .…”
Section: Resultscontrasting
confidence: 77%
“…It has been estimated the char carries metals like magnesium, calcium, potassium and iron at a significant level but however other heavy metals like zinc (Zn), chromium (Cr), nickel (Ni), molybdenum (Mo), manganese (Mn) and aluminum (Al) also present in negligible amounts. Certain sequential solvent extraction process helps in the significant removal of magnesium, calcium and potassium ( Lee et al, 2012 ).…”
Section: Pyrolysis An Effective Technique For Decomposing the Covid-1mentioning
confidence: 99%
“…Our study is presumably the first attempt to study the interactions between biochar and soil-dwelling mesofauna (springtails and mites), simultaneously in field and laboratory conditions. The low-temperature pine/wood chip biochar used in the experiment had a high carbon content but low surface area and ability for nutrient storage, which was in agreement with the findings of other authors (Lee et al 2016 ; Jiang et al 2017 ). The analysis of metal concentration did not report any chemical interference by biochar amendment in the agro-ecosystem.…”
Section: Discussionsupporting
confidence: 91%